2003
DOI: 10.1088/0953-8984/15/7/303
|View full text |Cite
|
Sign up to set email alerts
|

Optical spectroscopy and crystal-field analysis of YAl3(BO3)4single crystals doped with dysprosium

Abstract: YAl3 (BO3)4 crystals doped with Dy3+ were grown from a potassium trimolybdate flux. Their absorption and visible emission spectra and decay curves were measured at temperatures ranging from 10 to 298 K. The complete energy level scheme has been deduced from the low temperature measurements and reproduced by theoretical calculations based on a parametric Hamiltonian including coulombic, spin–orbit and crystal-field terms. The Judd–Ofelt parametrization scheme has been applied to the analysis of the room tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
28
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 23 publications
8
28
0
Order By: Relevance
“…These values are in good agreement with those reported for Er 3+ ions in other host [12,[17][18][19]. The Er 3+ free-ion parameters are also compared in Table 3 with those of Dy 3+ in the same host [16]. Considering only the contribution of the first coordination sphere around the Ln 3+ ion, this coordination sphere is composed of six equivalent O 2− ligands.…”
Section: Simulation Of the Energy Levelssupporting
confidence: 84%
See 3 more Smart Citations
“…These values are in good agreement with those reported for Er 3+ ions in other host [12,[17][18][19]. The Er 3+ free-ion parameters are also compared in Table 3 with those of Dy 3+ in the same host [16]. Considering only the contribution of the first coordination sphere around the Ln 3+ ion, this coordination sphere is composed of six equivalent O 2− ligands.…”
Section: Simulation Of the Energy Levelssupporting
confidence: 84%
“…It has been found that the fourth and sixth order CF parameters strongly differ from the corresponding ones in the best-fit set. This has been previously obtained for the two lanthanides Nd 3+ [15] and Dy 3+ [16] in the same host. This disagreement between the starting values and the final fit values was explicated by the contribution of the second coordination sphere around the Ln 3+ ion [16].…”
Section: Simulation Of the Energy Levelssupporting
confidence: 78%
See 2 more Smart Citations
“…Moreover, Dy 3+ -doped garnets have been indicated as potential saturable absorbers in the 2.8 m region [3]. As a consequence, the interest in the optical properties of Dy 3+ -doped oxides is considerably increasing currently [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%